Aerogel fabricated with halloysite nanoclay as ibuprofen and dexamethasone carrier for dual drugs release. (23rd August 2019) - Li, Hongyan; Sun, Cong; Liu, Hongli; Bai, Xiqing; Wang, Jiangang; Wei, Dongqing; Zhang, Baolian; Liao, Xiaolan; Li, Haiming; Li, Huan
Abstract: In this paper, halloysite (HNT) aerogels were prepared. Ibuprofen (IBU) and dexamethasone (DXMS) were loaded in the inner lumen of HNTs and the aerogel pores, respectively. Dual drug release behavior of HNT aerogels (HCAs) was researched. Characterizations of the samples were investigated by Fourier transform infrared spectrometer, thermogravimetric analysis, ultraviolet-visible spectra, microplate reader and so on. The results indicated that HCAs could allow controlled release of drugs. The release amount under acidic conditions is smaller than that of the alkaline environment. Koremeyer-Peppas model can nicely fit the IBU and DXMS release curves and the release follows Fickian diffusion. The dual drug release of HCAs had significant efficiency, and the dual release of HCAs can induce synergistic therapeutic effect to strengthen the cytotoxicity of mouse spleen lymphocytes. Dual drug loaded HCAs were compatible for normal mouse intestinal epithelial cells, which could be a good carrier of drugs.